Pengembangan Media Pembelajaran Matematika melalui Aplikasi Powtoon di Madrasah Ibtidaiyah (MI) Miftahut Thulab Brambang Karangawen - Aly Subkan; Winarno Winarno (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2020)
This research aims to develop innovative Mathematics learning media at Madrasah Ibtidaiyah (MI) Miftahut Thulab Brambang, Karangawen. This research was conducted to overcome the problem of lack of student learning motivation and to improve student learning outcomes MI Miftahut Thulab Brambang Karangawen in Mathematics subjects specifically KPK (Smallest Alliance Multiples) and FPB (Biggest Alliance Factors). This research belongs to the type of research and development (Research and Development) with the ADDIE model. The population used was grade IV MI Miftahut Thulab Brambang students, Karangawen. Data analysis uses quantitative description techniques. The results showed that the development of instructional media through powtoon was effectively used as an alternative media in delivering KPK and FPB material. The results of the application of the media illustrate the effectiveness of the media of learning mathematics through powtoon with an average grade grade up 45% from 60.5 to 87.5. The completeness value increased from 45% to 100%.